Interpatient variability in tamoxifen respone among breast cancer patient: the use of pharmacogenetics and metabolomics in closing the gaps in clinical practice / Nor Izwani Mohamed - Mohamed, Nor Izwani (Institute of Graduate Studies, UiTM, 2017)
Tamoxifen has been widely used as the standard adjuvant therapy for breast cancer patients with oestrogen receptor-positive status, especially in the highrisk pre- and postmenopausal women. However, 30 to 50% of ER-positive breast cancer patients do not respond to tamoxifen therapy. Major challenges to effective tamoxifen therapy include drug resistance, and adverse events. Thus, this study aims to investigate the impact of pharmacogenomics and metabolomics in monitoring the efficacy of tamoxifen treatment in BRCA patients. A total of 95 tamoxifen-treated patients, and 11 untreated breast cancer patients from three major Malaysian ethnic groups (Malay, Chinese and Indian) were recruited. However, only 84 tamoxifen-treated patients with completed clinical data were included for clinical association analysis.